The politics of international economic relations - Spero, Joan Edelman (Wadsworth. Cencage Learning, 2010)
THE POLITICS OF INTERNATIONAL ECONOMIC RELATIONS delivers the full breadth and depth of coverage readers need to truly understand the politics of today's world economy. Completely updated, the seventh edition reflects the sweeping changes that continue to reshape the international arena. It offers solid, contemporary coverage of political and economic relations, economic polarization in developing nations, and the roots of economic decline in centrally planned economies. An emphasis on the impact of globalization makes it ideal for equipping readers with a global perspective